Tüberküloz hastalarında yaşam kalitesi ölçülmesi ve Silymarin’in anti-tüberküloz ilaç kaynaklı hepatotokisite üzerine etkisinin deney hayvanlarında araştırılması - Shotorbani, Soudabeh Azarmir (My University, 2006)
1.ÖZET Çalışmamızın amacı, tüberküloz hastalarının yaşam kalitesini ölçmek ve silymarinin hepatoprotektif etkisi anti-tüberküloz ilaç kaynaklı hepatotoksisiteyi önlemedeki rolünü deneysel olarak araştırmaktır. Çalışmamızın birinci bölümünde, tüberküloz tanısı ile anti-tüberküloz tedavisi uygulanan 120 hastada, yaşam kaliteleri SF–36 ölçeğiyle ölçüldü. Ayakta tedavi gören hastalar (1. grup), ÇİD tüberkülozu olmayan ve yatarak tedavi gören hastalar (2. grup) ve ÇİD tüberkülozu olan ve yatarak tedavi gören hastalardan (3. grup) oluşan üç tedavi grubu ile sağlıklı kontrol grubu (4. grup) yaşam kalitesi indeksleri yönünden karşılaştırıldı. Çalışmanın ikinci bölümünde ise, her biri 10 sıçandan oluşan 6 gruba 14 gün süreyle şu tedavi uygulandı; 1.Grup: serum fizyolojik, 2. Grup: silymarin, 3. Grup: INH + RIF, 4. Grup: INH + RIF + PRZ, 5. Grup: INH + RIF + silymarin, 6.Grup: INH + RIF + PRZ + silymarin. Biyokimiyasal ve histopatolojik değerlendirmeler yapıldı. Çalışmamızın birinci bölümünde, rol fonksiyonu, sosyal fonksiyon ve rol emosyonel parametreleri yönünden gruplar arasında istatistiksel farklılıklar görüldü ve hastanede yatan hastaların yaşam kalitesi değerleri, ayakta tedavi gören hastaların ve sağlıklı bireylerin yaşam kalitesi değerlerinden daha düşük saptandı. Yaşam kalitesinin fiziksel ve mental boyut değerlerinin hasta gruplarındaki sıralaması 3., 2. ve 1. grup şeklinde saptandı. Çalışmamızın ikinci bölümünde, tedavi öncesi ve 14 günlük tedavi sonrası 3. ile 5. gruplar arasında ve 4. ile 6. gruplar arasında biyokimiyasal ve histopatolojik bulgular açısından istatistiksel farklılıklar görüldü. Tüberküloz, hastaların yaşam kalitelerini olumsuz yönde etkilemektedir. Bu durum özellikle hastanede yatan hastalarda ve ÇİD tüberkülozu olan hastalarda daha belirgin bir şekilde görülmektedir. Ayrıca deney hayvanlarda silymarinin anti-tüberküloz ilaçlara bağlı hepatotoksisiteye karşı koruyucu etkisi olduğu saptanmıştır. 2.

MEASUREMENT OF QUALITY OF LIFE IN PATIENTS WITH TUBERCULOSIS AND INVESTIGATION OF EFFICACY OF SILYMARIN IN ANTI-TUBERCULOSIS DRUGS INDUCED HEPATOTOXICITY IN EXPERIMENTAL ANIMALS The goal of our study is measuring the quality of life of patients with tuberculosis and examining hepatoprotective effects of silymarin in anti-tuberculosis drugs related hepatotoxicity experimentally. In first part of the study, patients with diagnosis of tuberculosis that receive anti-tuberculosis treatment, the quality of life has been measured by SF-36. Index of quality of life in three patient groups, out patients (1st group), hospitalized and not MDR tuberculosis patients (2nd group), hospitalized and MDR tuberculosis patients (3rd group) being compared with healthy control group (4th group). In second part of the study, healthy albino Vistar mice, examined in six treatments groups, each group having 10 mouse: 1st Group: serum fizyolojik, 2nd Group: silymarin, 3rd Group: INH + RIF, 4th Group: INH + RIF + PRZ, 5th Group: INH + RIF + silymarin, 6th Group: INH + RIF + PRZ + silymarin have been treated for the period of 14 days. Biochemical and histopathological values have been examined. In 120 cases which has been evaluated at the first part of our study, only role function, social function and role emotional parameters has been shown a significant statistical difference among these groups and the quality of life at the hospitalized patients has been measured less than the out patients and healthy control group. The measurement of physical and mental dimensions of quality of life in patient groups has been ranked respectively 1st, 2nd and 3rd group. At the second part of the study, biochemical and for the histopathological changes, before treatment and after 14-day period of treatment, between the 3th and 5th groups and the 4th and 6th groups a significant statistical difference has been seen. Tuberculosis, affects the quality of life in patients at the negative way. This situation in hospitalized patients and patients with MDR tuberculosis has seen more obviouesly. Additionally in experimental animals silymarin has protective effects in anti-tuberculosis related hepatotoxicity has been stablished. tuberculosis, quality of life, SF–36, silymarin, hepatotoxicity, clinical pharmacy.
Keywords: Bulaşıcı Hastalıklar; Hayvanlar, Deney_Bulaşıcı Hastalıklar; Tüberküloz